A rare case of discontinuous type splenogonadal fusion in a 13 year old boy: a case report and review of literature - Jonuzi, Asmir; Popović, Nusret; Zvizdić, Zlatan; Milišić, Emir; Bukvić, Melika; Sefić, Irmina; Džananović, Amra; Mesic, Amira; Chikha, Adisa; Zukanović, Amila; Kulovac, Benjamin (International Surgery Journal, 2020)
Splenogonadal fusion (SGF) is a rare developmental anomaly in which an abnormal connection between the splenic tissue and gonads or mesonephric derivatives is present. This entity often presents with scrotal mass, inguinal hernia, or cryptorchidism. Less than 200 cases have been reported since it was first described in 1883. It can be of continuous and discontinuous type based on the presence of a band of connecting splenic tissue. Report a rare case of discontinuous type of SGF in an adolescent male presenting as nonpalpable testis. On evaluation, ultrasonography (USG) and magnetic resonance imaging of abdomen and pelvis, his left scrotal testis was atrophied and right intra-abdominal undescended testis. This is the first reported case of SGF from Bosnia and Herzegovina. Laparoscopy was demonstrated to be the only accurate exploratory procedure for the diagnosis and surgical treatment of SGF with non‑palpable testis.